Identification of Potential Ebola Virus Nucleoprotein (EBOV NP) Inhibitor Derivate from Various Traditional Medicinal Plants in Indonesia: in silico study - Antonius, Yulanda; Ongko, Jeremi; Sukweenadhi, Johan; Putra, Sulistyo Emantoko Dwi (Fakultas Farmasi, Universitas Surabaya, 2021)
Ebola virus disease is caused by Ebolavirus infection. Within infection, Ebola nucleoprotein (EBOV NP) is essential part for virus proliferation. Recent report showed that the outbreak was happened in Congo on February 2021. Although million cases were reported, the drug is remain unavailable. However, Indonesia had a high diversity of plants as traditional drugs. This research aimed to identify the traditional drug plants as potential inhibitor for EBOV NP. The SMILE notation of 65 identified compounds were collected from PubChem and 3D structured of EBOV NP (PDB ID: 4Z9P) was obtained from PDB. Molecular docking was conducted between selected compounds and EBOV NP. Clabistrin C was selected as a control. Complex of compounds EBOV NP and its amino acid residues were depicted by using Chimera X and LigPlot. Several potential compounds were selected for pharmacological activity prediction by PASS Online, toxicity analysis by ProTox-II, and drug likeness analysis with SWISSADME. Result showed that among the docked compound, hesperidin, cucurbitacin, ginsenoside RH2, and ginsenoside RO had lower binding energy compared to control. Moreover, all of those compounds had comparable hydrogen and hydrophobic interactions with EBOV NP. Further analysis showed it has potential biological function for Ebola disease, such as antiviral, antioxidant, and immunostimulant. All those compounds had low toxicity. As conclusion, there are four promising compounds that potentially inhibited the Ebolavirus proliferation.